Fire safety in historic buildings: A case study using the qualitative risk analysis method - Yaman, Muammer; Kurtay, Cüneyt (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
Structural fires have long posed significant threats to human life, property, and societal stability. In the context of historic buildings, fires also risk the loss of irreplaceable cultural heritage. Ensuring fire safety in such structures requires a sensitive balance between risk mitigation and architectural conservation. This study investigates fire safety strategies in historic buildings through the restoration and renovation project of Bıçakçı Khan and Yıldız Cinema, two culturally significant structures in İzmir, Türkiye. Using Türkiye's Regulation on Fire Protection (TRFP) as the main guideline, a systematic fire safety control method was implemented through regulatory compliance checks, occupant load calculations, qualitative risk assessments (QRA), and evacuation route evaluations. The systematic fire safety control method adopts a two-step approach, in which the first step involves analysing occupant loads and architectural egress provisions, and the second step consists of conducting a qualitative risk analysis based on regulatory compliance. The study reveals that current fire safety regulations, while generally applicable, fall short in addressing the specific vulnerabilities of heritage structures. By applying a qualitative risk analysis, the research identifies the need for tailored strategies that prioritise both occupant safety and the preservation of architectural authenticity. Passive protection measures and low-impact interventions are proposed as effective means to enhance fire resilience in historic buildings. In conclusion, a systematic fire safety control method is proposed, emphasising minimal architectural intervention and the preservation of historical integrity. The study concludes with recommendations for revising current regulations and adopting performance-based approaches that integrate architectural, engineering, and conservation expertise, thereby ensuring both safety and cultural continuity.